2018
DOI: 10.21595/jve.2018.19935
|View full text |Cite
|
Sign up to set email alerts
|

Literature review of tire-pavement interaction noise and reduction approaches

Abstract: Tire-pavement interaction noise (TPIN) dominates for passenger vehicles with the speed of above 40 km/h and for trucks with the speed of 70 km/h. With the prevailing trend of electric vehicles, TPIN can become more NVH (Noise, Vibration, and Harshness) issue in the future. In this paper, the vehicle noise and tire noise were briefly reviewed in the background introduction. Then the motivation of and approaches to reducing tire noise was reviewed from open literature. It was found that the tire industry and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…(6). Many studies [1] and [2] have shown that the vibration noise produced by the front and rear of a tire coming into contact with the ground is asymmetrical. Therefore, the above five subareas must be studied separately.…”
Section: Fig 14 Tire Radial Deformation Distribution In the Noise Mmentioning
confidence: 99%
See 1 more Smart Citation
“…(6). Many studies [1] and [2] have shown that the vibration noise produced by the front and rear of a tire coming into contact with the ground is asymmetrical. Therefore, the above five subareas must be studied separately.…”
Section: Fig 14 Tire Radial Deformation Distribution In the Noise Mmentioning
confidence: 99%
“…Noise pollution produced by vehicles is a prominent issue in modern society, especially for the inhabitants of urban areas. Studies have shown that road traffic noise is a remarkably complex phenomenon, with different sources such as the power unit, aerodynamics, and tire-road interaction [1] and [2]. According to statistics, when heavy trucks travel at speeds of more than 70 km/h, tire noise becomes the main source of noise of a vehicle [3].…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the speed from 70 km/h to 50 km/h can reduce noise by more than 5dB. The study of the pavement type impact on the noise generated by the tyre is presented in publications [24] and [27]. Authors of [28] have presented the methodology for assessing noise at the interface between the road pavement and the tyre.…”
Section: Parameters and Indicatorsmentioning
confidence: 99%
“…There are 2 "A" segments made up of eight large pitches, 4 "B" segments made up of ten medium segments and 2 "C" segments made up of twelve small pitches. 4 Landers, 1982 [171] (US Patent 4327792)…”
Section: No Reference Tread Pattern Harmonic Spectrum Distribution Nmentioning
confidence: 99%